2019
DOI: 10.1002/jimd.12146
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological attributes of urea cycle disorders: A systematic review of the literature

Abstract: Urea cycle disorders (UCDs) are rare inherited metabolic conditions that impair the effectiveness of the urea cycle responsible for removing excess ammonia from the body. The estimated incidence of UCDs is 1:35 000 births, or approximately 113 new patients with UCD per year. This review summarizes neuropsychological outcomes among patients with the eight UCDs in reports published since 1980.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…This is not surprising, as patients with distal UCDs, especially those inclusive of the NBS population, tend to have milder disease courses less prone to hyperammonemia than the average proximal UCD patient. While some patients with “milder” disease may not need nitrogen scavenging therapy, studies have suggested that nitrogen scavenging therapy may confer some long-term neurocognitive benefits [ 31 ]. However, this was not evaluated in this study and represents a limitation to the data provided.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as patients with distal UCDs, especially those inclusive of the NBS population, tend to have milder disease courses less prone to hyperammonemia than the average proximal UCD patient. While some patients with “milder” disease may not need nitrogen scavenging therapy, studies have suggested that nitrogen scavenging therapy may confer some long-term neurocognitive benefits [ 31 ]. However, this was not evaluated in this study and represents a limitation to the data provided.…”
Section: Discussionmentioning
confidence: 99%
“…8 Arginase deficiency, which is among this group of diseases, has been reported much less frequently (1:950000). 9 Rapid-onset hyperammoniemia attacks are not characteristic for argininemia, they follow a slower clinical course. It may often present with growth retardation and pronounced progressive spasticity in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…If appropriate treatment is not initiated, patients will rapidly deteriorate and will be lost with cardiovascular collapse, respiratory failure and renal failure. 5,[8][9][10] This case was presented to draw attention to the case of argininemia, which was followed up with a diagnosis of cerebral palsy for a long time and lost the chance of early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ornithine Transcarbamylase (OTC) deficiency is an uncommon X‐linked inborn error of metabolism [1]. One study reported an incidence of in ~1 in 56,500 individuals [2]. Although it is rare, OTC deficiency represents the most common disorder of the urea cycle.…”
Section: Introductionmentioning
confidence: 99%